(untitled) (Bangladesh Journal of Urology, 2020)
Carcinoma prostate is a common disease in urological aspect. Diagnosis of prostate cancer has evolved through the past century. In additions to estimations of serum PSA which has more predictive value than diagnostic value. In previous days diagnosis of prostatic cancer relied on three measures - DRE, needle biopsy and open biopsy. With development of medical science different biopsy techniques have evolved for prostatic biopsy. Each techniques has its own merits and demerits. This review article presented here discusses on ultrasonoguided transrectal prostatic biopsy following intraprostatic local anaesthesia. A thorough review literature search was done to resolve theses issues and finally a recommendation is drawn to develop a recommendated policy of biopsy for accurate diagnosis of prostatic cancer. Bangladesh Journal of Urology, Vol. 16, No. 2, July 2013 p.57-62